The tribology between monocrystalline diamond and polycrystalline cubic boron nitride during frictional contact. (August 2021) - Müller, Ulrich; Kaiser, Josef; Barth, Sebastian; Bergs, Thomas
Abstract: The abrasive machining of superhard cutting tool materials such as polycrystalline cubic boron nitride is often conducted by grinding using diamond grinding wheels. Due to the high grinding wheel wear and the low material removal rates during grinding of polycrystalline cubic boron nitride, the manufacturing of this superhard material causes high production costs. The investigation of the tribology between diamond and polycrystalline cubic boron nitride enables to identify the cause-effect-relationships in the contact zone of the grinding wheel and the workpiece and thus to increase the process efficiency due to a knowledge-based process design. Hence, this paper presents an approach for the measurement of tribological process state variables and an empirical-analytical model to describe the tribological behavior during frictional contact of polycrystalline cubic boron nitride and diamond in cutting processes. The empirical-analytical model enables to calculate tribological process state variables such as the temperature of contact depending on the process input variables and the material properties of polycrystalline cubic boron nitride. Graphical abstract: Unlabelled Image Highlights: A test rig for tribological investigations between superhard materials was applied to a 5-axis machine tool The frictional contact of diamond and pcBN can be described based on an empirical-analytical model The friction coefficient was found to be very low (< 0.1) and decreases with increasing normal force and relative velocity Irreversible deformation of pcBN may occurs during frictional contact with diamond when high compressive stress is applied